‘Good Hunting’: German Submarine Offensives and South African Countermeasures off the South African Coast during the Second World War, 1942-1945 - Kleynhans, Evert (Scientia Militaria - South African Journal of Military Studies, 2016)
By the latter half of 1942, the High Command of the German U-boats (BdU) realised that the ‘sinking results’ of the North Atlantic had decreased immensely. The successes of the Allied anti-submarine operations in the North Atlantic precluded the successful employment of the German submarines in said waters. It was realised that the ‘sinking potential’ of the Cape Town–Freetown convoy route, in terms of tonnage, had increased exponentially by the latter half of 1942. This sudden increase was a direct result of the successful German submarine operations in the North Atlantic during 1939–1942. The first German submarine offensive in South African waters during 1942, Operation Eisbär, was aimed at striking a devastating blow to shipping off the South African coast. By the end of December 1942, an estimated 310 864 tons of shipping had been sunk through Operation Eisbär and the first U-cruiser operation alone. The success of Operation Eisbär led to a further two German submarine offensives being launched by the BdU in South African waters during the remainder of the Second World War, with a number of opportunistic attacks also made by submarines travelling to the Far East. This article has three specific aims. First, to discuss the Union Defence Force’s (UDF) threat perception and operational readiness in terms of the maritime defence of its coast, and the merchant shipping that rounded it, over the period September 1939 to October 1942. Second, to explain the nature and extent of the German submarine operations in South African waters[i]between October 1942 and February 1945. Last, the South African and Allied counter-measures to the German submarine threat off the South African coast will be discussed. By drawing from a myriad of primary archival sources, private and official correspondence, and a host of secondary sources, the background, nature, successes and failures of the German submarine operations, and the South African counter-measures are elucidated.